Needs and Perceptions of Patients With Dystonia During the COVID-19 Pandemic: A Qualitative Framework Analysis of Survey Responses From Italy - Rispoli, Vittorio; Díaz Crescitelli, Matías Eduardo; Cavallieri, Francesco; Antonelli, Francesca; Meletti, Stefano; Ghirotto, Luca; Valzania, Franco (Frontiers in Neurology, 2022)
Introduction Pandemic countermeasures have imposed both life and healthcare changes, prioritizing COVID-19-related management. The experience of patients suffering from rare diseases, such as dystonia, risks remaining understudied. Materials and Methods Using a framework analysis on a nationwide qualitative online survey, we sought to explore dystonic patients’ perspectives on their clinical assistance and possible unmet needs during the first pandemic wave. A survey consisting of 37 items (demographic characteristics, dystonia-related features, neurological service provision, therapeutic relationship with the neurologist, perceptions related to virus infection, perceptions about healthcare-related needs, work-related questions, information, and support-seeking during the pandemic) was organized in both closed- and opened-ended questions and diffused online. Results Responses from 62 participants were collected, most of them from the Italian red zones. Pandemic stemmed from harmful insides (virus spread and law impositions); social isolation was a relevant stressor. Motor and non-motor symptoms increased with detrimental consequences on the job and daily functionality. Outpatient clinics and rehabilitation sessions were shut down and, less frequently, even telephone/mail contacts. Despite efforts, dystonic patients felt alone in dealing with dystonia. Conclusion The first-wave pandemic-related condition had detrimental consequences on people living with dystonia, and relevant needs remained unmet. These findings may contribute to implementing the healthcare provision in the next steps of this or future pandemic.